Measurement of the central exclusive production of charged particle pairs in proton-proton collisions at √s = 200 GeV with the STAR detector at RHIC - STAR Collaboration (Journal of High Energy Physics, 2020)
We report on the measurement of the Central Exclusive Production of charged particle pairs h+h− (h = π, K, p) with the STAR detector at RHIC in proton-proton collisions at s$$ \sqrt{s} $$= 200 GeV. The charged particle pairs produced in the reaction pp → p′ + h+h− + p′ are reconstructed from the tracks in the central detector and identified using the specific energy loss and the time of flight method, while the forward-scattered protons are measured in the Roman Pot system. Exclusivity of the event is guaranteed by requiring the transverse momentum balance of all four final-state particles. Differential cross sections are measured as functions of observables related to the central hadronic final state and to the forward-scattered protons. They are measured in a fiducial region corresponding to the acceptance of the STAR detector and determined by the central particles’ transverse momenta and pseudorapidities as well as by the forward-scattered protons’ momenta. This fiducial region roughly corresponds to the square of the four-momentum transfers at the proton vertices in the range 0.04 GeV2 < −t1, −t2 < 0.2 GeV2, invariant masses of the charged particle pairs up to a few GeV and pseudorapidities of the centrally-produced hadrons in the range |η| < 0.7. The measured cross sections are compared to phenomenological predictions based on the Double Pomeron Exchange (DPE) model. Structures observed in the mass spectra of π+π− and K+K− pairs are consistent with the DPE model, while angular distributions of pions suggest a dominant spin-0 contribution to π+π− production. For π+π− production, the fiducial cross section is extrapolated to the Lorentz-invariant region, which allows decomposition of the invariant mass spectrum into continuum and resonant contributions. The extrapolated cross section is well described by the continuum production and at least three resonances, the f0(980), f2(1270) and f0(1500), with a possible small contribution from the f0(1370). Fits to the extrapolated differential cross section as a function of t1 and t2 enable extraction of the exponential slope parameters in several bins of the invariant mass of π+π− pairs. These parameters are sensitive to the size of the interaction region.
6 citations (Crossref) [2023-10-31] tex.ids: adamMeasurementCentralExclusive2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85089773182 type: Article
Keywords: Diffraction; Forward physics; Hadron-Hadron scattering (experiments); dept.phy; peer-reviewed